A formative evaluation of the Ballada Cinta innovation in birth registration: An administrative culture transformation - Alief Rizkia Ananda; Binti Azizatun Nafi’ah (Universitas Muhammadiyah Malang, 2025)
This study aims to evaluate the implementation of the Ballada Cinta Program (Newborns Immediately Receive Printed KIA and Birth Certificates) within the Department of Population and Civil Registration of Sampang Regency (Dispendukcapil), emphasizing the transformation of administrative culture and social participation among the Madurese community. The initiative was designed to simplify the issuance of birth certificates and Child Identity Cards through integrated services connecting village administrations and healthcare facilities. A qualitative descriptive approach was employed using Michael Scriven’s formative evaluation model, encompassing an analysis of program outcomes, goal attainment, and the adequacy of resource utilization. The units of analysis included villages, community health centers, and local community leaders. Findings indicate that, although there has been a significant increase in the ownership of birth certificates (95.66%) and the issuance of Child Identity Cards (39.54%), the program’s impact remains uneven. Several challenges persist, including limited digital infrastructure, disparities in administrative capacity across regions, staff turnover, and resistance toward modern bureaucratic systems. Culturally, collective birth reporting traditions and the dominance of family-based document processing have created resistance to digitalization and formal administrative procedures. Moreover, the existing digital divide between rural and urban areas affects service effectiveness, data accuracy, and user satisfaction. Penelitian ini bertujuan untuk mengevaluasi pelaksanaan Program Ballada Cinta (Bayi Lahir Langsung Cetak KIA dan Akta) di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Sampang, dengan menyoroti transformasi budaya administrasi dan partisipasi sosial masyarakat Madura. Program ini dirancang untuk mempermudah pengurusan akta kelahiran dan Kartu Identitas Anak (KIA) melalui integrasi layanan antara desa/kelurahan dan fasilitas kesehatan. Penelitian menggunakan pendekatan kualitatif deskriptif dengan model evaluasi formatif Michael Scriven, mencakup analisis hasil pelaksanaan program, ketercapaian tujuan, dan kesesuaian penggunaan sumber daya. Unit analisis mencakup desa, puskesmas, serta tokoh masyarakat lokal. Hasil menunjukkan bahwa meskipun terdapat peningkatan signifikan dalam kepemilikan akta kelahiran (95,66%) dan pencetakan KIA (39,54%), program ini belum sepenuhnya merata. Hambatan seperti keterbatasan infrastruktur digital, kesenjangan kapasitas antarwilayah, regenerasi petugas, dan resistensi terhadap sistem administrasi modern masih ditemukan. Secara budaya, tradisi pelaporan kelahiran secara kolektif dan dominasi peran keluarga dalam pengurusan dokumen menimbulkan resistensi terhadap proses digital dan birokrasi formal. Selain itu, Implikasi digital divide antara desa dan kota berdampak pada efektivitas layanan, akurasi data, serta kepuasan pengguna.